2018
DOI: 10.1186/s40478-018-0508-2
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid and ultra-sensitive quantitation of disease-associated α-synuclein seeds in brain and cerebrospinal fluid by αSyn RT-QuIC

Abstract: The diagnosis and treatment of synucleinopathies such as Parkinson disease and dementia with Lewy bodies would be aided by the availability of assays for the pathogenic disease-associated forms of α-synuclein (αSynD) that are sufficiently sensitive, specific, and practical for analysis of accessible diagnostic specimens. Two recent αSynD seed amplification tests have provided the first prototypes for ultrasensitive and specific detection of αSynD in patients’ cerebrospinal fluid. These prototypic assays requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
404
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 283 publications
(419 citation statements)
references
References 40 publications
9
404
4
2
Order By: Relevance
“…Therefore, the observed increase in the β-sheets content mirrors the RT-QuIC results, providing an unbiased validation of the formation of aggregates during the course of the reaction. Remarkably, Grovemann et al observed in CSF-seeded RT-QuIC reactions containing K23Q/ α-synuclein substrate that PD α-synuclein seeds exhibit lower signal responses in RT-QuIC when compared to DLB, 49 which confirms our findings. 43 Fibril compactness and size appeared increased in FCx-seeded reactions compared to reactions containing an SNc seed.…”
Section: Seeding Variability Of α-Synuclein and Potential Strain Diffsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the observed increase in the β-sheets content mirrors the RT-QuIC results, providing an unbiased validation of the formation of aggregates during the course of the reaction. Remarkably, Grovemann et al observed in CSF-seeded RT-QuIC reactions containing K23Q/ α-synuclein substrate that PD α-synuclein seeds exhibit lower signal responses in RT-QuIC when compared to DLB, 49 which confirms our findings. 43 Fibril compactness and size appeared increased in FCx-seeded reactions compared to reactions containing an SNc seed.…”
Section: Seeding Variability Of α-Synuclein and Potential Strain Diffsupporting
confidence: 92%
“…Importantly, because ThT affects the Raman signal, 48 all RT-QuIC reactions were prepared without adding ThT. Indeed, it has been recently demonstrated by different groups 43,49,50 that PD-derived α-synuclein possesses the ability to amplify recombinant α-synuclein when tested by RT-QuIC. Moreover, morphological studies conducted by AFM and TEM showed that DLB-seeded reactions may generate rod-shaped amyloid-fibrils of different sizes differing from other α-synuclein aggregates and exhibiting a more circular and compact appearance.…”
Section: Seeding Variability Of α-Synuclein and Potential Strain Diffmentioning
confidence: 99%
“…[1][2][3][4] However, in these studies, selected CSF samples or brain homogenates of clinically straightforward or neuropathologically confirmed cases were used. The high specificity and positive predictive values indicate that the vast majority of patients with an undefined diagnosis of parkinsonism and a positive α-syn RT-QuIC will have an underlying α-synucleinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, this test has thus far only been evaluated in clear-cut clinical cases and/or neuropathologically confirmed cases, whereas clinicians would rather use the test in ambiguous cases. [1][2][3][4] However, this test has thus far only been evaluated in clear-cut clinical cases and/or neuropathologically confirmed cases, whereas clinicians would rather use the test in ambiguous cases.…”
mentioning
confidence: 99%
“…With this initial screening approach, appropriate referrals can be made for subsequent specialty examinations and confirmatory diagnostic biomarkers (imaging, CSF), following the multistage models used for diagnosing cancer [31]. For example, Groveman et al [20] recently demonstrated the accuracy of a rapid and ultrasensitive seed amplification technique for detection of α‐synuclein. In the present proposed context, a blood‐based screening tool can be utilized to rule out the vast majority of patients who do not need to undergo lumbar puncture for biomarker confirmatory diagnostics.…”
Section: Introductionmentioning
confidence: 99%